Asymmetric Synthesis of Spiropyrazolones through Phosphine‐Catalyzed [4+1] Annulation1. (15th April 2014) - Han, Xiaoyu; Yao, Weijun; Wang, Tianli; Tan, Yong Ren; Yan, Ziyu; Kwiatkowski, Jacek; Lu, Yixin
Abstract An enantioselective synthesis of spiropyrazolones from allenoate‐derived MBH acetates and pyrazolones through a phosphine‐mediated [4+1] annulation process has been developed. Spiropyrazolones were readily prepared in good chemical yields and good to high enantioselectivities. This is the first asymmetric example in which α‐substituted allenoates were utilized as a C4 synthon for phosphine‐catalyzed [4+1] annulation.